IMPACT OF NON-BANKING FINANCIAL INSTITUTION ON SMALL SCALE ENTERPRISES IN BILSAPUR DISTRICT - Agrahari, Vaishali; Singh, Supriya (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The aim of this research paper is to find out the significant role of non- banking financial institutions (NBFIs) on small scale enterprises (SSEs) in the society which is a non- conventional financial sector which provides financial resources to small scale enterprises for their financial need. Based on the few literature, one objective and hypothesis has been formulated, linear regression in SPSS is used to find out the impact of dependent and independent variables, probability and simple random sampling method is used, a self-structured questionnaire was distributed among 58 respondents in Bilaspur district in order to find out the facts. This research paper provide the facts that there is a strong connection between NBFI and the growth of small scale enterprises in order to fulfill the requirement of finance time to time in the most organized manner which results growth and sustainability to the small scale enterprises.